Is it always so? Unexpected visions. (19th June 2020) - Deręgowski, Jan B.; Tatler, Benjamin W.
Abstract: If we consider perceptions as arising from predictive processes, we must consider the manner in which the underlying expectations are formed and how they are applied to the sensory data. We provide examples of cases where expectations give rise to unexpected and unlikely perceptions of the world. These examples may help define bounds for the notion that perceptual hypotheses are direct derivatives of experience and are used to furnish sensible interpretations of sensory data.